일미찰옥수수의 유묘기 저온에 따른 생육특성 변화 - 전승호; Seung Ho Jeon; 오승가; Seung Ka Oh; 김한용; Han Yong Kim; 나채인; Chae-in Na; 배희수; Hui Su Bae; 조영손; Young Son Cho (Korean journal of crop science, 2020)
To determine the damages to waxy corn caused by low temperature weather, we investigated the relationship between the temperature and duration of low temperature treatment and the changes in growth characteristics during the recovery period after the treatments in different growth periods. Growth inhibition started in the low temperature group treated at temperatures below 5℃ for three days. The inhibition ratio (IR) was more than 22% or more in all sample groups. As the treatment duration increased and the Temperature decreased, the growth was more greatly inhibited than that in the control. The IR was the highest at 27% or more in the 2nd leaf stage group treated at below 5℃ for 5 days. The IR was in the order of 2nd leaf stage > 1st leaf stage > coleoptile. The IR during recovery was the highest in the 2nd leaf stage group treated at -3℃ degree for 7 days, nd the values were 82% and 98% for NDVI and Fv/Fm, respectively. Especially, all groups treated at -3℃ showed either no changes or decreases in the growth characteristics. As a result, growth inhibition increased as the temperature decreased, and as the duration of the low temperature increased. The degree of damage was in the order of 2nd leaf stage > 1st leaf stage > coleoptile. All early seedlings stopped growing and withered when exposed to temperatures at or below -3℃ for 3 days or more.